Updating the morphological phylogenetics of Nopinae (Araneae: Caponiidae): novel terminals and characters, with two new species - Sánchez-Ruiz, Alexander; Bonaldo, Alexandre B. (European Journal of Taxonomy, 2024)
A re-analysis of the morphological phylogeny of the Nopinae is made, based on an update in the description of Aamunops Galán-Sánchez & Álvarez-Padilla, 2022 and the addition of the recently described genera Nopsma Sánchez-Ruiz, Brescovit & Bonaldo, 2020 and Roddemberryus Sánchez-Ruiz & Bonaldo, 2023. Two new species, Aamunops hoof sp. nov. (male) and Aamunops yiselae sp. nov. (male and female), are also described, which allows a better understanding of the genus morphology and resulted in an emended diagnosis. The description of Aamunops has been updated to include several characteristics of the ultrastructural morphology, legs, chelicerae, palps and female genitalia. The inclusion of these new characters of Aamunops along with those of Nopsma and Roddemberryus in the previous data matrix resulted in a new, completely different hypothesis of the relationships of the nopine genera: Nopsma is part of a group formed by Cubanops and Nyetnops, while Aamunops and Roddemberryus are grouped with representatives of Tarsonops. The four-eyed Nopsides ceralbonus Chamberlin, 1924 was recovered as the most basal species of Nopinae. The relationships among genera of Nopinae and the phylogenetic position of three species, whose taxonomic position is doubtful (Cubanops luquillo Sánchez-Ruiz, Brescovit & Alayón, 2015, Orthonops confuso Galán-Sánchez & Álvarez-Padilla, 2022 and Tarsonops irataylori Bond & Taylor, 2013), is also discussed.